READING AND WRITING INSIGHTS FOR CHILDREN - YUSUF JAFAR (International Journal of Innovations in Engineering Research and Technology, 2021)
Reading and writing are emphasized on the reform of intelligence education in childrens lives, the development of autonomous thinking, creativity, innovative thinking. The purpose of the discussion of this work emphasizes achievement how the development of reading and writing is, how the materials are involved, the time, preparation, learning strategies, media, and their relevance for reading and writing purposes